Klausa Dependen dan Fungsinya sebagai Objek Langsung dalam Naskah Film The Young Victoria - Rivani, Nadila; Geubrina, Misla (Universitas Harapan Medan, 2025)
This research analyzes the types of dependent clause and the function of dependent clause as a direct object in complex sentence found in The Young Victoria movie script. This research uses qualitative method to analyze the types of dependent clause by using the theory proposed by Miller (2002) and to analyze the function of dependent clause as a direct object by using the theory proposed by Aarts (2018). The data were clause taken from “The Young Victoria” movie script as source of data. To collect the data, the researchers took from library research. The results show that 75 complex sentence data were found clause, indicating three types of dependent clause. Starting with the least frequently found clause, the complement clause with 8 data, followed by the relative clause with 14 data, and the most frequently found clause, the adverbial clause with 53 data. Meanwhile, the function of dependent clause as a direct object was also found, with 6 data identified in this research.